Development of Digital Teaching Modules Based on Local Wisdom in Improving Elementary Student Literacy in Mover School Program - Rizal, Setria Utama; Syabrina, Muhammad; Mazrur, Mazrur; Asnafiyah, Asnafiyah; Sulaiman, Muhammad; Hamdi, Hamdi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
The purpose of this research is to develop a digital teaching module to improve student literacy. This research uses a type of study known as Research and Development (R&D), which aims to create a new product or improve an existing one. Specifically, this study follows the R&D methodology proposed by Thiagarajan (1974), which outlines the steps of research and development as a 4D model: Definition, Design, Develop, and Disseminate. The subjects of this study are six elementary school principals and six fourth-grade teachers in Palangka Raya City, East Kotawaringin Regency, and Kapuas Regency. To collect the necessary data, the researcher used observations, interviews, documentation, and questionnaires. The feasibility of digital teaching modules based on local wisdom is validated by subject matter experts and media (design) experts. According to the validation results from the validators, the material aspect received a rating of "Very Feasible" with a percentage of 87.6. The media aspect, based on validation by experts, received a rating of "Very Worthy" with a percentage of 80,4%. Based on the results of the trial, it shows more interest and attention to reading learning materials through their respective gadgets, so that the development of digital teaching modules based on local wisdom is able to increase student literacy in the SD/MI Mover School Program.